A proposed post-conflict planning model for US Army reconstruction teams - Weber, Bryan Douglas (Kansas State University, 2010)
As effects of social and environmental conflicts perpetuate globally, fewer nations in the world appear to be at settled peace. The on-set of natural disasters and socio-political conflicts continue to force the United States Government to be increasingly called upon to provide resources that secure unstable regions during times of conflict. One method the government uses to securing its international neighbors is through the deployment of US Army reconstruction teams. These teams assist in transforming a negatively impacted foreign nation into a peaceful and functioning sovereignty within itself and its region; however, in order to begin reconstruction and engage in long term stability for the best interest of the host-nation, the Army must scrutinize current decision-making techniques to assure that basic human rights are instilled and local inhabitants have a means to sustain those efforts. This research sets out to define a planning model which supplements Army doctrine concerning post-conflict reconstruction, mainly FM 3-07 Stability Operations. It looks to incorporate academia, professional experience, and government resources with indigenous leadership in order to define a process to reconstruct infrastructure for a foreign nation during a time of need. More importantly, it looks to enforce those measures which endorse the basic human rights of society to instill security in post-conflict regions.
Keywords: Planning; International Development; US Army; Military; Reconstruction & Development Model; Comprehensive Planning; Political Science, International Law and Relations (0616); Sociology, Social Structure and Development (0700); Urban and Regional Planning (0999)